Seleksi Galur Kacang Tanah Adaptif pada Lahan Kering Masam - Kasno, Astanto; Trustinah, Trustinah; Rahmiana, A. A. (Jurnal Penelitian Pertanian Tanaman Pangan, 2013)
Increasing production of groundnut through the opening of new land is considered as the best option available. The remaining land available for groundnut, however, is an acid dry land. Groundnut selection for acid soil tolerance through a preliminary yield test consisted of 100 advance lines was done in Natar Experimental Farm, Lampung, in the early dry season (MaretJuni) of 2010. The experiment was arranged in a randomized block design with three replications. The selected lines were then grown in South Lampung and East Lampung Districts during the late dry seasons (July-November) of 2010. The second experiment was done using a strip plot design with two replications. Applying the principal component analyses of 14 characters from the first experiment found nine characters that had KMO (Kaiser-MeyerOlkin) values higher than 0.5 and significant according to the Bartlett’s test. Six of the 9 characters had high loading factors, and they were competent for further analysis. To facilitate simultaneous selection of the six characters, a cluster analysis was applied and was able to distinguish lines into three groups consisted of 27, 24, and 39 lines respectively. Finally, 8, 1, and 17 lines were selected from each of the groups. Two check varieties, Landak and Turangga, were included in group one, while variety Jerapah was included in group three. Potential yields of the selected lines ranged from 2.5 to 3.6 t dry pods/ha with scores of leaf spot disease ranged from 4.7 to 6.0 (resistant to moderately resistant). Using 10% intensity of selection, 17 lines were selected that combined both locations test (low and high Al saturated). The selected lines will be tested further in an adaptation yield trial for two seasons in various locations prior to the release as new varieties adapted to dry acid soil.